Studi Literatur Implementasi Fatwa DSN-MUI Nomor B-578/DSN-MUI/XI/2020 Tentang Penerapan CashWaqf Linked Sukuk di Indonesia - Arifin, Muhammad Haikal; Nurhidayat, Muhammad Fadhil; Afifah, Rumaisha Tsamaratul; Muzdhalifah, Shafiyyah (Department of Islamic Economics Law, 2025)
This study aims to determine the implementation of the MUI DSN Fatwa No. B-578/DSN-MUI/IX/2020 on the implementation of Cash Waqaf Linked sukuk: B-578/DSN-MUI/IX/2020 concerning the application of Cash Waqaf Linked sukuk, the method used in this research is the literature review method. This research uses a qualitative approach to 16 articles including journals and fiscal year projects and found 16 relevant articles on the implementation of sukuk in accordance with the existing fatwa. Researchers obtained secondary data on the Google Scholar platform. Based on the results of research conducted by researchers on 16 articles in the form of journals and theses using the literature review method, there are still several journals that need to further study the application of sukuk in Indonesia, so that the results of the study are still vague, while those that are in accordance with the application of the fatwa are 16 journals that state that they are appropriate.